Mexico : Country Financial Accountability Assessment - World Bank (Washington, DC, 2013)
This Country Financial Accountability Assessment (CFAA) summarizes the status of implementation of financial management measures of the Federal public sector, showing both strengths, and areas for improvement, and, reflects input contributions in each area of public management. The main strength observed was the existence of clear rules governing the Federal Government's administrative financial transactions, highlighted by a federal public administration with rigorous internal control systems, evidence of the Government's decision to fight against corruption, and improper administrative practices. The main strengths of the budget system are associated with the existence of a well-defined, regulated and documented mandatory procedure for all execution phases. Conversely, weaknesses of the budget system are complex procedures resulting from the large number of documents, laws, rules, decrees, circulars and instructions that, diminish the efficiency, and effectiveness of budget management. Regarding the Treasury function, its strength is the systematic internal order under which it performs its functions of custody, concentration, oversight and application of federal funds. Federal government accounting registers, and reports a reliable and timely position of the public accounts, and its main strengths are associated with a well-defined, regulated and documented mandatory procedure for all phases, supported by a sound legal and regulatory framework. Recommendations outline the promotion of integrated budget management systems into a single database; the use of an appropriate number of indicators reflecting planned results and goals achieved, to allow for the follow up of multi-annual investment processes; promotion of a greater simplification of the regulatory framework for budget management; that automated and integrated management require a comprehensive review of the organizational structures, functions, and operations; and, to establish mechanisms for the executing entities to evaluate investments based on cost-benefit criteria, to prioritize investments, and improve the efficiency with which State resources are allocated.